ARE COMMUNICATION STRATEGIES FREQUENTLY USED IN SPEAKING CLASS? - Wicaksono, Agung (English Teaching Journal, 2014)
Communication strategy is the way to help the speakers when facing difficulties in communication using English as a second language. This case study, at the first year students of English Department, aims to know the most frequent studentsâ strategies to communicate in speaking activity in speaking class. It is Â found that thirteen communication strategies were used by the students in speaking English class, but not all of the communication strategies were used in every conversation, but only certain communication strategy was used. It depends on Â the materials difficulties. Furhermore, the most frequentÂ  communication strategies is stalling or time gaining strategy. As they need some time to think and then continue talking after they find the right words they need to communicate. This findings is in line with the propossed theory stated that communication strategy is defined as a systematic technique employed by a speaker to express his or her meaning when facing certain difficulties in communication.